Insights into Local Tumor Microenvironment Immune Factors Associated with Regression of Cutaneous Melanoma Metastases by Mycobacterium bovis Bacille Calmette–Guérin - Yang, Junbao; Jones, Maris S.; Ramos, Romela Irene; Chan, Alfred A.; Lee, Agnes F.; Foshag, Leland J.; Sieling, Peter A.; Faries, Mark B.; Lee, Delphine J. (Frontiers in Oncology, 2017)
Mycobacterium bovis Bacille Calmette-Guerin (BCG) is listed as an intralesional therapeutic option for inoperable stage III in-transit melanoma in the National Comprehensive Cancer Network Guidelines. Although the mechanism is unknown, others have reported up to 50% regression of injected lesions and 17% regression of uninjected lesions in immunocompetent patients have been reported after direct injection of BCG into metastatic melanoma lesions in the skin. BCG and other mycobacteria express ligands capable of stimulating the g9d2 T cells. Therefore, we hypothesized that g9d2 T cells play a role in promoting BCG-mediated antitumor immunity in patients treated with intralesional BCG for in-transit cutaneous melanoma metastases. Indeed, we found g9d2 T cell infiltration in melanoma skin lesions during the course of ILBCG treatment. Gene expression analysis revealed that BCG injection elicits the expression of a vast array of chemokines in tumor lesions, including strong expression of CXCL9, 10, and 11, a set of chemokines that attract T cells expressing the CXCR3 chemokine receptor. In corroboration with our hypothesis, approximately 85% of gd T cells express high levels of CXCR3 on their surface. Importantly, the injected tumor lesions also express genes whose protein products are the antigenic ligands for gd T cells (BTN3A1 and MICB), and the cytokines that are the typical products of activated gd T cells. Interestingly, we also found that gd T cells infiltrate the regressed lesions which did not receive BCG injections. Our study suggests that g9d2 T cells may contribute to melanoma regression induced by ILBCG treatment.